Medium-entropy alloy and preparation method and application thereof
Patent Information
- Application Number
- CN202411564918.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-03-07
- Estimated Expiration
- Not applicable · inactive patent
Smart Images

Figure CN119571171A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of alloy materials, and in particular relates to a medium-entropy alloy and a preparation method and application thereof. Background Art
[0002] Modern high-end cryogenic equipment, such as space rocket liquid engines and nuclear fusion reactors, have an urgent need for ultra-high strength and toughness metal structural materials for ultra-low temperatures. The currently used 1Cr18Ni9Ti, 304 and 316 stainless steels have insufficient comprehensive mechanical properties, which seriously restricts the performance improvement of high-end cryogenic equipment. The NiCoFeCr-based high entropy alloy strengthened by nano-L12 phase precipitation and the NiCoCr-based medium entropy alloy strengthened by nano-L12 phase precipitation both have excellent ultra-low temperature strong and tough comprehensive mechanical properties, which can meet the actual needs of modern high-end cryogenic equipment. In comparison, the NiCoCr-based medium entropy alloy strengthened by nano-L12 phase precipitation has more excellent comprehensive mechanical properties.
[0003] To improve the ultra-low temperature mechanical strength of the NiCoCr-based medium entropy alloy strengthened by precipitation of nano-L12 phase, the following aspects can be considered: (1) Precipitation strengthening: Through reasonable composition design, medium entropy alloys can be induced to form strengthening phases. For example, in NiCoCr high entropy alloys, by adding appropriate amounts of elements such as Al and Ti, the nano-L12 phase is induced to form through subsequent aging heat treatment, which is coherent with the matrix of the face-centered cubic crystal structure. Therefore, the phase interface mismatch degree and stress are low, which can produce excellent precipitation strengthening effect. (2) Lattice resistance strengthening: For example, the lattice resistance of NiCoCr medium entropy alloy is about 218MPa. The lattice resistance can be improved by adding large-sized atoms such as Mo and V to cause lattice distortion, but it is easy to cause the appearance of brittle phases such as σ phase and Laveas phase. (3) Grain refinement strengthening: By controlling rolling deformation and heat treatment, the grain size can be adjusted. Grain boundary defects can hinder dislocation movement and thus strengthen the alloy. In addition, by adding appropriate elements to increase the Hall-Petch coefficient, the grain refinement strengthening effect can also be improved.
[0004] However, medium-entropy alloys have many components, and adding multiple elements can easily induce the formation of brittle phases, which in turn damages the toughness of the alloy. Therefore, the composition design of high-strength and tough alloys is challenging. Invention patent CN115927944A mentions that the medium-entropy alloy (NiCoCr) is significantly improved by vanadium microalloying. 76 (Ni6AlTi)3 lattice resistance, thereby improving the ultra-low temperature mechanical strength. Although 3% vanadium content can significantly improve the mechanical properties, it inhibits the formation of deformation twins and stacking faults to a certain extent, damaging the toughness. When the vanadium content increases to 6%, the deformation twins and stacking faults are strongly inhibited, seriously damaging the toughness of the alloy.
[0005] Because alloy materials need to be used in ultra-low temperature environments, medium-entropy alloys not only have the common problem of not being able to balance strength and toughness, but also have alloy properties that are significantly different from those at room temperature. Currently, there is little research on the performance of alloy materials for ultra-low temperature applications, which makes it difficult to meet the urgent demand for high-performance ultra-low temperature structural materials in aerospace rocket liquid engine components or other fields. Summary of the invention
[0006] The purpose of the present invention is to overcome the problems existing in the above-mentioned prior art and to provide a medium-entropy alloy and a preparation method and application thereof.
[0007] The present invention is achieved through the following technical solutions:
[0008] In a first aspect, the present invention provides a medium entropy alloy, wherein the medium entropy alloy is (NiCoCr) in atomic percentage. 76-2x Hf x Ta x (Ni6AlTi)3, where 0<x≤4.
[0009] The present invention is a medium entropy alloy (NiCoCr) 76 (Ni6AlTi)3 is used as the matrix, and Hf and Ta elements are added to the alloy at the same time to achieve the coordinated control of high strength and high toughness: the addition of Ta can reduce the stacking fault energy, and will not completely inhibit the deformation twins and stacking faults of the medium entropy alloy; Ta element also has an excellent hysteresis diffusion effect, which can delay the growth of nano L12 phase particles during heat treatment, thereby producing a strong precipitation strengthening effect. The addition of Hf can cause lattice resistance strengthening, but will increase the stacking fault energy. Adding Hf and Ta elements at the same time can comprehensively strengthen the lattice resistance and precipitation strengthening effects, and will not cause excessive increase in stacking fault energy. The co-addition of Al and Ti elements in the medium-entropy alloy of the present invention can induce the formation of nano L12 precipitation phase, thereby enhancing the mechanical properties of the medium-entropy alloy; the co-addition of Hf and Ta elements can further improve the lattice resistance and precipitation strengthening effect, thereby greatly improving the mechanical properties of the medium-entropy alloy, so that it has both good tensile plasticity and strength at an ultra-low temperature of 77K, thereby making up for the problem that the strength and toughness of existing alloys cannot be taken into account at the same time, providing a new component selection for the medium-entropy alloy, and meeting the urgent demand for high-performance metal structural materials for ultra-low temperature use in liquid engines in the aerospace field.
[0010] As a preferred embodiment of the medium entropy alloy of the present invention, the medium entropy alloy is (NiCoCr) 74 HfTa(Ni6AlTi)3,(NiCoCr) 72 Hf2Ta2(Ni6AlTi)3,(NiCoCr) 70 Hf3Ta3(Ni6AlTi)3,(NiCoCr) 68At least one of Hf4Ta4(Ni6AlTi)3.
[0011] In a second aspect, the present invention provides a medium-entropy alloy material, wherein the medium-entropy alloy material comprises the medium-entropy alloy.
[0012] The medium-entropy alloy material obtained by the medium-entropy alloy atomic composition of the present invention has excellent mechanical properties and toughness at ultra-low temperatures and can be applied to a variety of ultra-low temperature metal material application scenarios.
[0013] As a preferred embodiment of the medium entropy alloy material of the present invention, the medium entropy alloy material is a medium entropy alloy plate.
[0014] As a preferred embodiment of the medium-entropy alloy material of the present invention, the medium-entropy alloy material is a medium-entropy alloy heterogeneous joint.
[0015] As a preferred embodiment of the medium-entropy alloy material of the present invention, the medium-entropy alloy heterogeneous joint is obtained by welding the medium-entropy alloy and stainless steel.
[0016] Preferably, the stainless steel comprises 316 stainless steel.
[0017] The medium-entropy alloy of the present invention not only has excellent ultra-low temperature mechanical properties, but also has excellent welding properties. The heterogeneous joint obtained by welding the medium-entropy alloy of the present invention with stainless steel also has excellent ultra-low temperature strong and tough comprehensive mechanical properties, which can meet the working conditions requirements of structural parts such as fusion reactors and hydrogen energy.
[0018] In a third aspect, the present invention provides a method for preparing the medium entropy alloy material, comprising the following steps:
[0019] (1) weighing Co, Cr, Ni, Hf, Ta, Al and Ti metal raw materials according to atomic percentage, melting, casting, and solution heat treatment to obtain a medium entropy alloy ingot;
[0020] (2) processing the medium entropy alloy ingot obtained in step (1) into a medium entropy alloy ingot plate, and cold rolling the medium entropy alloy ingot plate to obtain a medium entropy alloy cold-rolled plate;
[0021] (3) subjecting the medium-entropy alloy cold-rolled sheet obtained in step (2) to aging heat treatment to obtain the medium-entropy alloy material.
[0022] The preparation method of the medium-entropy alloy material of the present invention can obtain a fine-grained structure through cold rolling and aging heat treatment, thereby making full use of the fine-grained strengthening effect to improve the mechanical strength of the medium-entropy alloy. Aging heat treatment can induce the precipitation of nano L12 precipitation phase, and the precipitation of nano L12 phase can play a strengthening role. At the same time, the precipitate can also prevent the coarsening of the grains, making the grains more refined and improving the mechanical strength of the medium-entropy alloy. In addition, the addition of Hf and Ta elements can comprehensively strengthen the lattice resistance and precipitation strengthening effects, and finally obtain a medium-entropy alloy with extremely excellent mechanical strength and toughness at low temperatures. The preparation method of the present invention is relatively simple and convenient, and the obtained medium-entropy alloy material can meet the urgent demand for high-performance ultra-low temperature structural materials for aerospace rocket liquid engine components, and provides a new direction for the preparation of high-performance large-scale and complex-shaped medium-entropy alloy materials.
[0023] As a preferred embodiment of the method for preparing the medium entropy alloy of the present invention, in the step (1), the temperature of the solution heat treatment is 1100°C-1150°C, and the time is 4h-48h.
[0024] More preferably, the solution heat treatment is carried out at a temperature of 1150° C. and for a time of 4 hours.
[0025] As a preferred embodiment of the method for preparing the medium-entropy alloy of the present invention, in the step (2), the thickness of the medium-entropy alloy ingot plate is 10mm-30mm; the cold rolling adopts multiple passes of cold rolling, the pressing amount of each pass is 0.2mm-0.5mm, and the total deformation is 70%-90%.
[0026] As a preferred embodiment of the method for preparing the medium entropy alloy of the present invention, in the step (3), the temperature of the aging heat treatment is 600°C-900°C, and the time is 4h-500h.
[0027] More preferably, the temperature of the aging heat treatment is 700°C-900°C, and the time is 18h-48h; further, the temperature of the aging heat treatment is 700°C, and the time is 24h.
[0028] The conditions of aging heat treatment will affect the application of medium-entropy alloys in ultra-low temperature environments. The present invention has found through research that the medium-entropy alloys obtained under the above-mentioned aging heat treatment conditions have good mechanical strength and toughness.
[0029] Preferably, in step (1), the smelting is vacuum smelting, and the vacuum smelting is: using a magnetic levitation induction melting furnace to perform smelting 2 or 3 times, wherein the voltage of the magnetic levitation induction melting furnace is controlled to be 550V, the current is 450-480A, and the time of each smelting is 15-20min.
[0030] Preferably, in step (1), the metal raw material is metal single substance particles, the purity of the metal single substance particles is 99.5%-99.97%, and the particle size is 2mm-10mm.
[0031] Preferably, in step (1), the metal raw material is pretreated, and the pretreatment includes pickling, ethanol cleaning under ultrasonic conditions, and vacuum drying.
[0032] Preferably, a method for preparing the medium-entropy alloy plate comprises the following steps: obtaining a medium-entropy alloy cold-rolled plate according to the steps (1) and (2), then electron beam welding the obtained medium-entropy alloy cold-rolled plate, and then performing aging heat treatment according to the step (3) to obtain the medium-entropy alloy plate.
[0033] Preferably, in the method for preparing the medium-entropy alloy plate, the welding voltage of the electron beam welding is 150 kV, the welding current is 7.5 mA, and the welding speed is 600 mm / min.
[0034] Preferably, a method for preparing the medium-entropy alloy heterogeneous joint comprises the following steps: obtaining a medium-entropy alloy cold-rolled plate according to the steps (1) and (2), and then electron beam welding the obtained medium-entropy alloy cold-rolled plate with stainless steel to obtain the medium-entropy alloy heterogeneous joint.
[0035] Preferably, in the method for preparing the medium-entropy alloy heterogeneous joint, the welding voltage of the electron beam welding is 150 kV, the welding current is 6.0 mA, and the welding speed is 600 mm / min.
[0036] In a fourth aspect, the present invention provides the medium-entropy alloy and the use of the medium-entropy alloy material in the preparation of metal materials.
[0037] The present invention has the following beneficial effects: the present invention gives full play to the effects of lattice resistance strengthening, precipitation strengthening and fine grain strengthening through cold rolling, aging heat treatment and addition of Hf and Ta elements, while improving the mechanical strength of the medium-entropy alloy and maintaining good toughness. The co-addition of Hf and Ta elements can improve the lattice resistance and precipitation strengthening effects, the co-addition of Al and Ti elements can induce the formation of nano L12 precipitation phase, and multiple strengthening methods synergistically improve the mechanical properties of the medium-entropy alloy. The low stacking fault energy enables the alloy to have multiple deformation modes such as dislocation slip, stacking fault, deformation twinning, etc. at ultra-low temperatures, so that it has good tensile plasticity at ultra-low temperatures of 77K, providing new ideas for improving the ultra-low temperature mechanical properties of existing alloy materials. It also provides new component selections for medium-entropy alloys, meeting the urgent demand for high-performance metal structural materials for ultra-low temperatures for liquid engines in the aerospace field. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1It is a schematic diagram of the preparation process of the entropy alloy material in the present invention;
[0039] Figure 2 This is a morphology diagram of the medium-entropy alloy nano-precipitation phase obtained in Example 6 of the present invention;
[0040] Figure 3 This is a morphology diagram of the medium-entropy alloy nano-precipitation phase obtained in Example 8 of the present invention;
[0041] Figure 4 This is a grain morphology diagram of the medium-entropy alloy obtained in Example 8 of the present invention. DETAILED DESCRIPTION
[0042] To better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be understood by those skilled in the art that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0043] Unless otherwise specified, the experimental methods used in the examples are all conventional methods; the materials, reagents, etc. used, unless otherwise specified, can be obtained from commercial channels.
[0044] The raw materials used in the following examples and comparative examples are all metal raw materials with a purity of ≥99.95%, and the component raw materials used in each parallel experiment are of the same kind. Figure 1 shown.
[0045] Example 1
[0046] A medium entropy alloy material, the composition of the medium entropy alloy material is (NiCoCr) 74 HfTa(Ni6AlTi)3, wherein each element is expressed in atomic percentage.
[0047] The method for preparing the medium entropy alloy material comprises the following steps:
[0048] (1) Before smelting, the Co, Cr, Ni, Hf, Ta, Al and Ti metal raw materials are cleaned by acid washing, ultrasonic alcohol cleaning and vacuum drying respectively;
[0049] Press (NiCoCr) 74 The atomic percentage of HfTa(Ni6AlTi)3 is converted into mass. Accurately weigh the clean metal elements of Co, Cr, Ni, Hf, Ta, Al and Ti to the nearest 0.1 mg.
[0050] All metal raw materials were placed in a magnetic levitation induction melting furnace for vacuum melting. The voltage was controlled at 550V and the current was controlled at 450A. The melting was performed three times, each time for 20 minutes. After the melting was completed, the alloy melt was cast into a copper mold and cooled to obtain a medium entropy alloy (NiCoCr). 74 HfTa(Ni6AlTi)3 ingot; subjecting the ingot to solution heat treatment, keeping the ingot at 1150°C for 4 hours, and then quenching and cooling in water to obtain a medium entropy alloy ingot;
[0051] (2) using wire cutting, the medium entropy alloy ingot obtained in step (1) is processed into a 10 mm thick disc, and then cold-rolled at room temperature, using multiple cold rolling processes, with a total deformation of 80%, and a pressing amount of 0.2 mm each time. The sample temperature becomes high during each cold rolling process, and water is used for cooling to obtain a medium entropy alloy cold-rolled sheet;
[0052] (3) The medium entropy alloy cold-rolled sheet obtained in step (2) is subjected to aging heat treatment at a temperature of 700° C. for 24 h to finally obtain (NiCoCr) 74 HfTa(Ni6AlTi)3 medium entropy alloy material.
[0053] The obtained (NiCoCr) 74 The HfTa(Ni6AlTi)3 medium entropy alloy has a temperature of 5×10 -4 The test was carried out at a strain rate of / s, and the test results were as follows: the yield strength was 1813MPa, the tensile strength was 2075MPa, and the elongation was 15.2%.
[0054] Example 2
[0055] A medium entropy alloy material, the composition of the medium entropy alloy material is (NiCoCr) 74 HfTa(Ni6AlTi)3, wherein each element is expressed in atomic percentage.
[0056] The difference between the preparation method of the entropy alloy material in this embodiment and that in Embodiment 1 is that in the step (3), the temperature of the aging heat treatment is 800° C., and the other preparation parameters are the same as those in Embodiment 1.
[0057] The obtained (NiCoCr) 74 The HfTa(Ni6AlTi)3 medium entropy alloy has a temperature of 5×10 -4 The test was carried out at a strain rate of / s, and the test results were as follows: the yield strength was 1617MPa, the tensile strength was 1978MPa, and the elongation was 19.6%.
[0058] Example 3
[0059] A medium entropy alloy material, the composition of the medium entropy alloy material is (NiCoCr) 74 HfTa(Ni6AlTi)3, wherein each element is expressed in atomic percentage.
[0060] The difference between the preparation method of the entropy alloy material in this embodiment and that in Embodiment 1 is that in the step (3), the temperature of the aging heat treatment is 900° C., and the other preparation parameters are the same as those in Embodiment 1.
[0061] The obtained (NiCoCr) 74 The HfTa(Ni6AlTi)3 medium entropy alloy has a temperature of 5×10 -4 The test was carried out at a strain rate of / s, and the test results were as follows: the yield strength was 1182MPa, the tensile strength was 1632MPa, and the elongation was 29.6%.
[0062] Example 4
[0063] A medium entropy alloy material, the composition of the medium entropy alloy material is (NiCoCr) 72 Hf2Ta2(Ni6AlTi)3, wherein each element is expressed in atomic percentage.
[0064] The method for preparing the medium entropy alloy material comprises the following steps:
[0065] (1) Before smelting, the Co, Cr, Ni, Hf, Ta, Al and Ti metal raw materials are cleaned by acid washing, ultrasonic alcohol cleaning and vacuum drying respectively;
[0066] Press (NiCoCr) 72 The atomic percentage of Hf2Ta2(Ni6AlTi)3 is converted into mass. Accurately weigh the clean metal elements of Co, Cr, Ni, Hf, Ta, Al and Ti to the nearest 0.1 mg.
[0067] All metal raw materials were placed in a magnetic levitation induction melting furnace for vacuum melting. The voltage was controlled at 550V and the current was controlled at 450A. The melting was performed three times, each time for 20 minutes. After the melting was completed, the alloy melt was cast into a copper mold and cooled to obtain a medium entropy alloy (NiCoCr). 72 Hf2Ta2(Ni6AlTi)3 ingot; subjecting the ingot to solution heat treatment, keeping the ingot at 1150°C for 4 hours, and then quenching and cooling in water to obtain a medium entropy alloy ingot;
[0068] (2) using wire cutting, the medium entropy alloy ingot obtained in step (1) is processed into a 10 mm thick disc, and then cold-rolled at room temperature, using multiple cold rolling processes, with a total deformation of 80%, and a pressing amount of 0.2 mm each time. The sample temperature becomes high during each cold rolling process, and water is used for cooling to obtain a medium entropy alloy cold-rolled sheet;
[0069] (3) The medium entropy alloy cold-rolled sheet obtained in step (2) is subjected to aging heat treatment at a temperature of 700° C. for 24 h to finally obtain (NiCoCr) 72 Hf2Ta2(Ni6AlTi)3 medium entropy alloy material.
[0070] The obtained (NiCoCr) 72 The Hf2Ta2(Ni6AlTi)3 medium entropy alloy has a temperature of 5×10 -4 The test was carried out at a strain rate of / s, and the test results were as follows: the yield strength was 1918MPa, the tensile strength was 2136MPa, and the elongation was 6.9%.
[0071] Example 5
[0072] A medium entropy alloy material, the composition of the medium entropy alloy material is (NiCoCr) 72 Hf2Ta2(Ni6AlTi)3, wherein each element is expressed in atomic percentage.
[0073] The difference between the preparation method of the entropy alloy material in this embodiment and that in Embodiment 4 is that in the step (3), the temperature of the aging heat treatment is 600° C., and the other preparation parameters are the same as those in Embodiment 4.
[0074] The obtained (NiCoCr) 72 The Hf2Ta2(Ni6AlTi)3 medium entropy alloy has a temperature of 5×10 -4 The test was carried out at a strain rate of / s, and the test results were as follows: the yield strength was 2190MPa, the tensile strength was 2299MPa, and the elongation was 2.1%.
[0075] Example 6
[0076] A medium entropy alloy material, the composition of the medium entropy alloy material is (NiCoCr) 72 Hf2Ta2(Ni6AlTi)3, wherein each element is expressed in atomic percentage.
[0077] The difference between the preparation method of the entropy alloy material in this embodiment and that in Embodiment 4 is that in the step (3), the temperature of the aging heat treatment is 800° C., and the other preparation parameters are the same as those in Embodiment 4.
[0078] The nano-precipitation phase morphology of the medium entropy alloy obtained in this embodiment is shown in FIG. Figure 2 As shown, the obtained (NiCoCr) 72 The Hf2Ta2(Ni6AlTi)3 medium entropy alloy has a temperature of 5×10 -4 The test was carried out at a strain rate of / s, and the test results were as follows: the yield strength was 1765MPa, the tensile strength was 2010MPa, and the elongation was 8.9%.
[0079] Example 7
[0080] A medium entropy alloy material, the composition of the medium entropy alloy material is (NiCoCr) 72 Hf2Ta2(Ni6AlTi)3, wherein each element is expressed in atomic percentage.
[0081] The difference between the preparation method of the entropy alloy material in this embodiment and that in Embodiment 4 is that in the step (3), the temperature of the aging heat treatment is 850°C, and the other preparation parameters are the same as those in Embodiment 4.
[0082] The obtained (NiCoCr) 72 The Hf2Ta2(Ni6AlTi)3 medium entropy alloy has a temperature of 5×10 -4 The test was carried out at a strain rate of / s, and the test results were as follows: the yield strength was 1518MPa, the tensile strength was 1902MPa, and the elongation was 16.8%.
[0083] Example 8
[0084] A medium entropy alloy material, the composition of the medium entropy alloy material is (NiCoCr) 72 Hf2Ta2(Ni6AlTi)3, wherein each element is expressed in atomic percentage.
[0085] The difference between the preparation method of the entropy alloy material in this embodiment and that in Embodiment 4 is that in the step (3), the temperature of the aging heat treatment is 900° C., and the other preparation parameters are the same as those in Embodiment 4.
[0086] The nano-precipitation phase morphology of the medium entropy alloy obtained in this embodiment is shown in FIG. Figure 3 The grain morphology is shown in Figure 4 As shown, the obtained (NiCoCr) 72 The Hf2Ta2(Ni6AlTi)3 medium entropy alloy has a temperature of 5×10 -4 The test was carried out at a strain rate of / s, and the test results were as follows: the yield strength was 1382MPa, the tensile strength was 1752MPa, and the elongation was 23.9%.
[0087] Example 9
[0088] A medium entropy alloy material, the composition of the medium entropy alloy material is (NiCoCr) 70 Hf3Ta3(Ni6AlTi)3, wherein each element is expressed in atomic percentage.
[0089] The method for preparing the medium entropy alloy material comprises the following steps:
[0090] (1) Before smelting, the Co, Cr, Ni, Hf, Ta, Al and Ti metal raw materials are cleaned by acid washing, ultrasonic alcohol cleaning and vacuum drying respectively;
[0091] Press (NiCoCr) 70 The atomic percentage of Hf3Ta3(Ni6AlTi)3 is converted into mass. Accurately weigh the clean metal elements of Co, Cr, Ni, Hf, Ta, Al and Ti to the nearest 0.1 mg.
[0092] All metal raw materials were placed in a magnetic levitation induction melting furnace for vacuum melting. The voltage was controlled at 550V and the current was controlled at 450A. The melting was performed three times, each time for 20 minutes. After the melting was completed, the alloy melt was cast into a copper mold and cooled to obtain a medium entropy alloy (NiCoCr). 70 Hf3Ta3(Ni6AlTi)3 ingot; subjecting the ingot to solution heat treatment, keeping the ingot at 1150°C for 4 hours, and then quenching and cooling in water to obtain a medium entropy alloy ingot;
[0093] (2) using wire cutting, the medium entropy alloy ingot obtained in step (1) is processed into a 10 mm thick disc, and then cold-rolled at room temperature, using multiple cold rolling processes, with a total deformation of 80%, and a pressing amount of 0.2 mm each time. The sample temperature becomes high during each cold rolling process, and water is used for cooling to obtain a medium entropy alloy cold-rolled sheet;
[0094] (3) The medium entropy alloy cold-rolled sheet obtained in step (2) is subjected to aging heat treatment at a temperature of 700° C. for 24 h to finally obtain (NiCoCr) 70 Hf3Ta3(Ni6AlTi)3 medium entropy alloy material.
[0095] The obtained (NiCoCr) 70 The Hf3Ta3(Ni6AlTi)3 medium entropy alloy has a temperature of 5×10 -4 The test was carried out at a strain rate of / s, and the test results were as follows: the yield strength was 1992MPa, the tensile strength was 2167MPa, and the elongation was 2.3%.
[0096] Example 10
[0097] A medium entropy alloy material, the composition of the medium entropy alloy material is (NiCoCr) 70 Hf3Ta3(Ni6AlTi)3, wherein each element is expressed in atomic percentage.
[0098] The difference between the preparation method of the entropy alloy material in this embodiment and that in Embodiment 9 is that in the step (3), the temperature of the aging heat treatment is 800° C., and the other preparation parameters are the same as those in Embodiment 9.
[0099] The obtained (NiCoCr) 70 The Hf3Ta3(Ni6AlTi)3 medium entropy alloy has a temperature of 5×10 -4 The test was carried out at a strain rate of / s, and the test results were as follows: the yield strength was 1849MPa, the tensile strength was 2044MPa, and the elongation was 6.3%.
[0100] Embodiment 11
[0101] A medium entropy alloy material, the composition of the medium entropy alloy material is (NiCoCr) 70 Hf3Ta3(Ni6AlTi)3, wherein each element is expressed in atomic percentage.
[0102] The difference between the preparation method of the entropy alloy material in this embodiment and that in Embodiment 9 is that in the step (3), the temperature of the aging heat treatment is 900° C., and the other preparation parameters are the same as those in Embodiment 9.
[0103] The obtained (NiCoCr) 70 The Hf3Ta3(Ni6AlTi)3 medium entropy alloy has a temperature of 5×10 -4 The test was carried out at a strain rate of / s, and the test results were as follows: the yield strength was 1559MPa, the tensile strength was 1806MPa, and the elongation was 9.8%.
[0104] Example 12
[0105] A medium entropy alloy material, the composition of the medium entropy alloy material is (NiCoCr) 68 Hf4Ta4(Ni6AlTi)3, wherein each element is expressed in atomic percentage.
[0106] The method for preparing the medium entropy alloy material comprises the following steps:
[0107] (1) Before smelting, the Co, Cr, Ni, Hf, Ta, Al and Ti metal raw materials are cleaned by acid washing, ultrasonic alcohol cleaning and vacuum drying respectively;
[0108] Press (NiCoCr) 68The atomic percentage of Hf4Ta4(Ni6AlTi)3 is converted into mass. Accurately weigh the clean metal elements of Co, Cr, Ni, Hf, Ta, Al and Ti to the nearest 0.1 mg.
[0109] All metal raw materials were placed in a magnetic levitation induction melting furnace for vacuum melting. The voltage was controlled at 550V and the current was controlled at 450A. The melting was performed three times, each time for 20 minutes. After the melting was completed, the alloy melt was cast into a copper mold and cooled to obtain a medium entropy alloy (NiCoCr). 68 Hf4Ta4(Ni6AlTi)3 ingot; subjecting the ingot to solution heat treatment, keeping the ingot at 1150°C for 4 hours, and then quenching and cooling in water to obtain a medium entropy alloy ingot;
[0110] (2) using wire cutting, the medium entropy alloy ingot obtained in step (1) is processed into a 10 mm thick disc, and then cold-rolled at room temperature, using multiple cold rolling processes, with a total deformation of 80%, and a pressing amount of 0.2 mm each time. The sample temperature becomes high during each cold rolling process, and water is used for cooling to obtain a medium entropy alloy cold-rolled sheet;
[0111] (3) The medium entropy alloy cold-rolled sheet obtained in step (2) is subjected to aging heat treatment at a temperature of 800° C. for 24 h to finally obtain (NiCoCr) 68 Hf4Ta4(Ni6AlTi)3 medium entropy alloy material.
[0112] The obtained (NiCoCr) 68 The Hf4Ta4(Ni6AlTi)3 medium entropy alloy has a temperature of 5×10 -4 The test was carried out at a strain rate of / s, and the test results were as follows: the yield strength was 2035MPa, the tensile strength was 2198MPa, and the elongation was 4.2%.
[0113] Embodiment 13
[0114] A medium entropy alloy material, the composition of the medium entropy alloy material is (NiCoCr) 68 Hf4Ta4(Ni6AlTi)3, wherein each element is expressed in atomic percentage.
[0115] The difference between the preparation method of the entropy alloy material in this embodiment and that in Embodiment 12 is that in the step (3), the temperature of the aging heat treatment is 900°C, and the other preparation parameters are the same as those in Embodiment 12.
[0116] The obtained (NiCoCr) 68 The Hf4Ta4(Ni6AlTi)3 medium entropy alloy has a temperature of 5×10 -4The test was carried out at a strain rate of / s, and the test results were as follows: the yield strength was 1774MPa, the tensile strength was 1989MPa, and the elongation was 6.8%.
[0117] Embodiment 14
[0118] A medium entropy alloy plate, the composition of the medium entropy alloy plate is (NiCoCr) 74 HfTa(Ni6AlTi)3, wherein each element is expressed in atomic percentage.
[0119] The method for preparing the medium entropy alloy plate comprises the following steps:
[0120] (1) Before smelting, the Co, Cr, Ni, Hf, Ta, Al and Ti metal raw materials are cleaned by acid washing, ultrasonic alcohol cleaning and vacuum drying respectively;
[0121] Press (NiCoCr) 74 The atomic percentage of HfTa(Ni6AlTi)3 is converted into mass. Accurately weigh the clean metal elements of Co, Cr, Ni, Hf, Ta, Al and Ti to the nearest 0.1 mg.
[0122] All metal raw materials were placed in a magnetic levitation induction melting furnace for vacuum melting. The voltage was controlled at 550V and the current was controlled at 450A. The melting was performed three times, each time for 20 minutes. After the melting was completed, the alloy melt was cast into a copper mold and cooled to obtain a medium entropy alloy (NiCoCr). 74 HfTa(Ni6AlTi)3 ingot; subjecting the ingot to solution heat treatment, keeping the ingot at 1150°C for 4 hours, and then quenching and cooling in water to obtain a medium entropy alloy ingot;
[0123] (2) using wire cutting, the medium entropy alloy ingot obtained in step (1) is processed into a 10 mm thick disc, and then cold-rolled at room temperature, using multiple cold rolling processes, with a total deformation of 80%, and a pressing amount of 0.2 mm each time. The sample temperature becomes high during each cold rolling process, and water is used for cooling to obtain a medium entropy alloy cold-rolled sheet;
[0124] (3) The medium entropy alloy cold-rolled sheet obtained in step (2) is cleaned and polished to a thickness of 2 mm, and then a medium entropy alloy cold-rolled sheet with a width of 55 mm and a length of 105 mm is cut out by electric spark wire cutting, and the cut section is polished cleanly with sandpaper to remove the processing oxide layer, and then the two cold-rolled sheets are butt-welded by electron beam welding, with a welding voltage of 150 kV, a welding current of 7.5 mA, and a welding speed of 600 mm / min. After welding, the length of the sheet is 105 mm, the width is 110 mm, and the thickness is 2 mm. Then, an aging heat treatment is performed at a temperature of 900° C. for 24 h to finally obtain (NiCoCr)74 HfTa(Ni6AlTi)3 medium entropy alloy sheet.
[0125] The obtained (NiCoCr) 74 HfTa(Ni6AlTi)3 medium entropy alloy sheet at 77K with a temperature of 5×10 -4 The test was carried out at a strain rate of / s, and the test results were as follows: the yield strength was 872MPa, the tensile strength was 1457MPa, and the elongation was 21.6%.
[0126] Embodiment 15
[0127] A medium entropy alloy heterogeneous joint, the medium entropy alloy heterogeneous joint comprising a medium entropy alloy and 316 stainless steel, wherein the composition of the medium entropy alloy is (NiCoCr) 74 HfTa(Ni6AlTi)3, wherein each element is expressed in atomic percentage.
[0128] The method for preparing the medium-entropy alloy heterogeneous joint comprises the following steps:
[0129] (1) Before smelting, the Co, Cr, Ni, Hf, Ta, Al and Ti metal raw materials are cleaned by acid washing, ultrasonic alcohol cleaning and vacuum drying respectively;
[0130] Press (NiCoCr) 74 The atomic percentage of HfTa(Ni6AlTi)3 is converted into mass. Accurately weigh the clean metal elements of Co, Cr, Ni, Hf, Ta, Al and Ti to the nearest 0.1 mg.
[0131] All metal raw materials were placed in a magnetic levitation induction melting furnace for vacuum melting. The voltage was controlled at 550V and the current was controlled at 450A. The melting was performed three times, each time for 20 minutes. After the melting was completed, the alloy melt was cast into a copper mold and cooled to obtain a medium entropy alloy (NiCoCr). 74 HfTa(Ni6AlTi)3 ingot; subjecting the ingot to solution heat treatment, keeping the ingot at 1150°C for 4 hours, and then quenching and cooling in water to obtain a medium entropy alloy ingot;
[0132] (2) using wire cutting, the medium entropy alloy ingot obtained in step (1) is processed into a 10 mm thick disc, and then cold-rolled at room temperature, using multiple cold rolling processes, with a total deformation of 80%, and a pressing amount of 0.2 mm each time. The sample temperature becomes high during each cold rolling process, and water is used for cooling to obtain a medium entropy alloy cold-rolled sheet;
[0133] (3) The medium entropy alloy cold-rolled sheet obtained in step (2) and the commercial 316 austenitic stainless steel sheet were cleaned with an alcohol acetone solution, and then electron beam welded at a welding voltage of 150 kV, a welding current of 6.0 mA, and a welding speed of 600 mm / min to finally obtain (NiCoCr) 74 HfTa(Ni6AlTi)3 medium entropy alloy heterogeneous joint.
[0134] The obtained (NiCoCr) 74 The HfTa(Ni6AlTi3 medium entropy alloy heterojunction was 5×10 -4 The test was carried out at a strain rate of / s, and the test results were as follows: the yield strength was 500 MPa, the tensile strength was 945 MPa, and the elongation was 22.4%.
[0135] Comparative Example 1
[0136] A medium entropy alloy material, the composition of the medium entropy alloy material is (CoCrNi) 76 (Ni6AlTi)3, wherein each element is expressed in atomic percentage.
[0137] The method for preparing the medium entropy alloy material comprises the following steps:
[0138] (1) Before smelting, the Co, Cr, Ni, Al and Ti metal raw materials are cleaned by acid washing, ultrasonic alcohol cleaning and vacuum drying respectively;
[0139] Press(CoCrNi) 76 The atomic percentage of (Ni6AlTi)3 is converted into mass. The clean metal elements of Co, Cr, Ni, Al and Ti are accurately weighed to the nearest 0.1 mg.
[0140] All metal raw materials were placed in a magnetic levitation induction melting furnace for vacuum melting. The voltage was controlled at 550 V, the current was controlled at 450 A, and the melting was performed three times, each melting lasting 20 minutes. After the melting was completed, the alloy melt was cast into a copper mold and cooled to obtain a medium entropy alloy (CoCrNi). 76 (Ni6AlTi)3 ingot; subjecting the ingot to solution heat treatment, keeping the ingot at 1150°C for 4 hours, and then quenching and cooling in water to obtain a medium entropy alloy ingot;
[0141] (2) using wire cutting, the medium entropy alloy ingot obtained in step (1) is processed into a 10 mm thick disc, and then cold-rolled at room temperature, using multiple cold rolling processes, with a total deformation of 80%, and a pressing amount of 0.2 mm each time. The sample temperature becomes high during each cold rolling process, and water is used for cooling to obtain a medium entropy alloy cold-rolled sheet;
[0142] (3) The medium entropy alloy cold-rolled sheet obtained in step (2) is subjected to aging heat treatment at a temperature of 700° C. for 24 h to finally obtain (CoCrNi) 76 (Ni6AlTi)3 medium entropy alloy material.
[0143] The obtained (CoCrNi) 76 (Ni6AlTi)3 medium entropy alloy at 77K with a temperature of 5×10 -4 The test was carried out at a strain rate of / s, and the test results were as follows: the yield strength was 1637MPa, the tensile strength was 1982MPa, and the elongation was 18%.
[0144] Comparative Example 2
[0145] A medium entropy alloy material, the composition of the medium entropy alloy material is (NiCoCr) 76 (Ni6AlTi)3, wherein each element is expressed in atomic percentage.
[0146] The difference between the preparation method of the entropy alloy material in this comparative example and that in comparative example 2 is that in the step (3), the temperature of the aging heat treatment is 900° C., and the other preparation parameters are the same as those in comparative example 1.
[0147] The obtained (NiCoCr) 76 (Ni6AlTi)3 medium entropy alloy at 77K with a temperature of 5×10 -4 The test was carried out at a strain rate of / s, and the test results were as follows: the yield strength was 1035MPa, the tensile strength was 1587MPa, and the elongation was 37.7%.
[0148] Comparative Example 3
[0149] A medium entropy alloy material, the composition of the medium entropy alloy material is (NiCoCr) 75 Hf(Ni6AlTi)3, wherein each element is expressed in atomic percentage.
[0150] The method for preparing the medium entropy alloy material comprises the following steps:
[0151] (1) Before smelting, the Co, Cr, Ni, Hf, Al and Ti metal raw materials are cleaned by acid washing, ultrasonic alcohol cleaning and vacuum drying respectively;
[0152] Press (NiCoCr) 75 The atomic percentage of Hf(Ni6AlTi)3 is converted into mass. Accurately weigh the clean metal elements of Co, Cr, Ni, Hf, Al and Ti to the nearest 0.1 mg.
[0153] All metal raw materials were placed in a magnetic levitation induction melting furnace for vacuum melting. The voltage was controlled at 550V and the current was controlled at 450A. The melting was performed three times, each time for 20 minutes. After the melting was completed, the alloy melt was cast into a copper mold and cooled to obtain a medium entropy alloy (NiCoCr). 75 Hf(Ni6AlTi)3 ingot; subjecting the ingot to solution heat treatment, keeping the ingot at 1150°C for 4 hours, and then quenching and cooling in water to obtain a medium entropy alloy ingot;
[0154] (2) using wire cutting, the medium entropy alloy ingot obtained in step (1) is processed into a 10 mm thick disc, and then cold-rolled at room temperature, using multiple cold rolling processes, with a total deformation of 80%, and a pressing amount of 0.2 mm each time. The sample temperature becomes high during each cold rolling process, and water is used for cooling to obtain a medium entropy alloy cold-rolled sheet;
[0155] (3) The medium entropy alloy cold-rolled sheet obtained in step (2) is subjected to aging heat treatment at a temperature of 900° C. for 24 h to finally obtain (NiCoCr) 75 Hf(Ni6AlTi)3 medium entropy alloy material.
[0156] The obtained (NiCoCr) 75 The Hf(Ni6AlTi)3 medium entropy alloy has a temperature of 5×10 -4 The test was carried out at a strain rate of / s, and the test results were as follows: the yield strength was 1092MPa, the tensile strength was 1562MPa, and the elongation was 28.4%.
[0157] Comparative Example 4
[0158] A medium entropy alloy material, the composition of the medium entropy alloy material is (NiCoCr) 75 Ta(Ni6AlTi)3, wherein each element is expressed in atomic percentage.
[0159] The method for preparing the medium entropy alloy material comprises the following steps:
[0160] (1) Before smelting, the Co, Cr, Ni, Ta, Al and Ti metal raw materials are cleaned by acid washing, ultrasonic alcohol cleaning and vacuum drying respectively;
[0161] Press (NiCoCr) 75 The atomic percentage of Ta(Ni6AlTi)3 is converted into mass. Accurately weigh the clean metal elements of Co, Cr, Ni, Ta, Al and Ti to the nearest 0.1 mg.
[0162] All metal raw materials were placed in a magnetic levitation induction melting furnace for vacuum melting. The voltage was controlled at 550V and the current was controlled at 450A. The melting was performed three times, each time for 20 minutes. After the melting was completed, the alloy melt was cast into a copper mold and cooled to obtain a medium entropy alloy (NiCoCr). 75 Ta(Ni6AlTi)3 ingot; subjecting the ingot to solution heat treatment, keeping the ingot at 1150°C for 4 hours, and then quenching and cooling in water to obtain a medium entropy alloy ingot;
[0163] (2) using wire cutting, the medium entropy alloy ingot obtained in step (1) is processed into a 10 mm thick disc, and then cold-rolled at room temperature, using multiple cold rolling processes, with a total deformation of 80%, and a pressing amount of 0.2 mm each time. The sample temperature becomes high during each cold rolling process, and water is used for cooling to obtain a medium entropy alloy cold-rolled sheet;
[0164] (3) The medium entropy alloy cold-rolled sheet obtained in step (2) is subjected to aging heat treatment at a temperature of 900° C. for 24 h to finally obtain (NiCoCr) 75 Ta(Ni6AlTi)3 medium entropy alloy material.
[0165] The obtained (NiCoCr) 75 The Ta(Ni6AlTi)3 medium entropy alloy has a temperature of 5×10 -4 The test was carried out at a strain rate of / s, and the test results were as follows: the yield strength was 1104MPa, the tensile strength was 1574MPa, and the elongation was 28.7%.
[0166] Comparative Example 5
[0167] A medium entropy alloy material, the composition of the medium entropy alloy material is (NiCoCr) 74 ZrTa(Ni6AlTi)3, wherein each element is expressed in atomic percentage.
[0168] The method for preparing the medium entropy alloy material comprises the following steps:
[0169] (1) Before smelting, the Co, Cr, Ni, Zr, Ta, Al and Ti metal raw materials are cleaned by acid washing, ultrasonic alcohol cleaning and vacuum drying respectively;
[0170] Press (NiCoCr) 74 The atomic percentage of ZrTa(Ni6AlTi)3 is converted into mass. Accurately weigh the clean metal elements of Co, Cr, Ni, Zr, Ta, Al and Ti to the nearest 0.1 mg.
[0171] All metal raw materials were placed in a magnetic levitation induction melting furnace for vacuum melting. The voltage was controlled at 550V and the current was controlled at 450A. The melting was performed three times, each time for 20 minutes. After the melting was completed, the alloy melt was cast into a copper mold and cooled to obtain a medium entropy alloy (NiCoCr). 74 ZrTa(Ni6AlTi)3 ingot; subjecting the ingot to solution heat treatment, keeping the ingot at 1150°C for 4 hours, and then quenching and cooling in water to obtain a medium entropy alloy ingot;
[0172] (2) using wire cutting, the medium entropy alloy ingot obtained in step (1) is processed into a 10 mm thick disc, and then cold-rolled at room temperature, using multiple cold rolling processes, with a total deformation of 80%, and a pressing amount of 0.2 mm each time. The sample temperature becomes high during each cold rolling process, and water is used for cooling to obtain a medium entropy alloy cold-rolled sheet;
[0173] (3) The medium entropy alloy cold-rolled sheet obtained in step (2) is subjected to aging heat treatment at a temperature of 900° C. for 24 h to finally obtain (NiCoCr) 74 ZrTa(Ni6AlTi)3 medium entropy alloy material.
[0174] The obtained (NiCoCr) 74 The ZrTa(Ni6AlTi)3 medium entropy alloy has a temperature of 5×10 -4 The test was carried out at a strain rate of / s, and the test results were as follows: the yield strength was 1134MPa, the tensile strength was 1595MPa, and the elongation was 27.6%.
[0175] Comparative Example 6
[0176] A medium entropy alloy material, the composition of the medium entropy alloy material is (NiCoCr) 74 HfZr(Ni6AlTi)3, wherein each element is expressed in atomic percentage.
[0177] The method for preparing the medium entropy alloy material comprises the following steps:
[0178] (1) Before smelting, the Co, Cr, Ni, Hf, Zr, Al and Ti metal raw materials are cleaned by acid washing, ultrasonic alcohol cleaning and vacuum drying respectively;
[0179] Press (NiCoCr) 74 The atomic percentage of HfZr(Ni6AlTi)3 is converted into mass. Accurately weigh the clean metal elements of Co, Cr, Ni, Hf, Ta, Al and Ti to the nearest 0.1 mg.
[0180] All metal raw materials were placed in a magnetic levitation induction melting furnace for vacuum melting. The voltage was controlled at 550V and the current was controlled at 450A. The melting was performed three times, each time for 20 minutes. After the melting was completed, the alloy melt was cast into a copper mold and cooled to obtain a medium entropy alloy (NiCoCr). 74 HfZr(Ni6AlTi)3 ingot; subjecting the ingot to solution heat treatment, keeping the ingot at 1150°C for 4 hours, and then quenching and cooling in water to obtain a medium entropy alloy ingot;
[0181] (2) using wire cutting, the medium entropy alloy ingot obtained in step (1) is processed into a 10 mm thick disc, and then cold-rolled at room temperature, using multiple cold rolling processes, with a total deformation of 80%, and a pressing amount of 0.2 mm each time. The sample temperature becomes high during each cold rolling process, and water is used for cooling to obtain a medium entropy alloy cold-rolled sheet;
[0182] (3) The medium entropy alloy cold-rolled sheet obtained in step (2) is subjected to aging heat treatment at a temperature of 900° C. for 24 h to finally obtain (NiCoCr) 74 HfZr(Ni6AlTi)3 medium entropy alloy material.
[0183] The obtained (NiCoCr) 74 The HfZr(Ni6AlTi)3 medium entropy alloy has a temperature of 5×10 -4 The test was carried out at a strain rate of / s, and the test results were as follows: the yield strength was 1112MPa, the tensile strength was 1565MPa, and the elongation was 26.9%.
[0184] Comparative Example 7
[0185] A medium entropy alloy material, the composition of the medium entropy alloy material is (NiCoCr) 66 Hf5Ta5(Ni6AlTi)3, wherein each element is expressed in atomic percentage.
[0186] The method for preparing the medium entropy alloy material comprises the following steps:
[0187] (1) Before smelting, the Co, Cr, Ni, Hf, Ta, Al and Ti metal raw materials are cleaned by acid washing, ultrasonic alcohol cleaning and vacuum drying respectively;
[0188] Press (NiCoCr) 66 The atomic percentage of Hf5Ta5(Ni6AlTi)3 is converted into mass. Accurately weigh the clean metal elements of Co, Cr, Ni, Hf, Ta, Al and Ti to the nearest 0.1 mg.
[0189] All metal raw materials were placed in a magnetic levitation induction melting furnace for vacuum melting. The voltage was controlled at 550V and the current was controlled at 450A. The melting was performed three times, each time for 20 minutes. After the melting was completed, the alloy melt was cast into a copper mold and cooled to obtain a medium entropy alloy (NiCoCr). 66 Hf5Ta5(Ni6AlTi)3 ingot; subjecting the ingot to solution heat treatment, keeping the ingot at 1150°C for 4 hours, and then quenching and cooling in water to obtain a medium entropy alloy ingot;
[0190] (2) using wire cutting, the medium entropy alloy ingot obtained in step (1) is processed into a 10 mm thick disc, and then cold-rolled at room temperature, using multiple cold rolling processes, with a total deformation of 80%, and a pressing amount of 0.2 mm each time. The sample temperature becomes high during each cold rolling process, and water is used for cooling to obtain a medium entropy alloy cold-rolled sheet;
[0191] (3) The medium entropy alloy cold-rolled sheet obtained in step (2) is subjected to aging heat treatment at a temperature of 900° C. for 24 h to finally obtain (NiCoCr) 66 Hf5Ta5(Ni6AlTi)3 medium entropy alloy material.
[0192] The obtained (NiCoCr) 66 The Hf5Ta5(Ni6AlTi)3 medium entropy alloy has a temperature of 5×10 -4 The test was carried out at a strain rate of / s, and the test results were as follows: the yield strength was 1974MPa, the tensile strength was 2012MPa, and the elongation was 1.9%.
[0193] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A medium entropy alloy, characterized in that: The medium entropy alloy is (NiCoCr) in atomic percentage 76-2x Hf x Ta x (Ni6AlTi)3, where 0<x≤4.
2. The medium entropy alloy according to claim 1, characterized in that: The medium entropy alloy is (NiCoCr) 74 HfTa(Ni6AlTi)3,(NiCoCr) 72 Hf2Ta2(Ni6AlTi)3,(NiCoCr) 70 Hf3Ta3(Ni6AlTi)3,(NiCoCr) 68 At least one of Hf4Ta4(Ni6AlTi)3.
3. A medium entropy alloy material, characterized in that: The medium-entropy alloy material includes the medium-entropy alloy described in claim 1 or 2.
4. The medium-entropy alloy material according to claim 3, characterized in that: The medium-entropy alloy material is a medium-entropy alloy plate.
5. The medium-entropy alloy material according to claim 3, characterized in that: The medium-entropy alloy material is a medium-entropy alloy heterogeneous joint.
6. The medium-entropy alloy material according to claim 5, characterized in that: The medium-entropy alloy heterogeneous joint is obtained by welding the medium-entropy alloy and stainless steel.
7. A method for preparing the medium-entropy alloy material according to claim 3, characterized in that: The following steps are involved: (1) weighing Co, Cr, Ni, Hf, Ta, Al and Ti metal raw materials according to atomic percentage, melting, casting, and solution heat treatment to obtain a medium entropy alloy ingot; (2) processing the medium entropy alloy ingot obtained in step (1) into a medium entropy alloy ingot plate, and cold rolling the medium entropy alloy ingot plate to obtain a medium entropy alloy cold-rolled plate; (3) subjecting the medium-entropy alloy cold-rolled sheet obtained in step (2) to aging heat treatment to obtain the medium-entropy alloy material.
8. The method for preparing a medium-entropy alloy material according to claim 7, characterized in that: In the step (1), the temperature of the solution heat treatment is 1100°C-1150°C, and the time is 4h-48h; and / or, in the step (3), the temperature of the aging heat treatment is 600°C-900°C, and the time is 4h-500h.
9. The method for preparing a medium-entropy alloy material according to claim 7, characterized in that: In the step (2), the thickness of the medium entropy alloy ingot plate is 10 mm-30 mm; the cold rolling adopts multiple cold rolling passes, the pressing amount of each pass is 0.2 mm-0.5 mm, and the total deformation amount is 70%-90%.
10. Use of the medium-entropy alloy according to claim 1 or 2, or the medium-entropy alloy material according to any one of claims 3 to 6 in the preparation of metal materials.
Citation Information
Patent Citations
Medium-entropy alloy and preparation method thereof
CN115927944A